Essentials of management science - Islam, Rafikul (Thomson Learning, 2005)
The basic purpose of writing the present text is to enhance the readability of Management Science textbook. The distinguishing feature of the book is that it is written in an utmost lucid manner so that even an average student can grasp the subject matter easily. Every chapter has started with excerpts from a case study. This is purported to convince the reader about the real-world applicability of the techniques to be discussed thereafter. Further, at the end of every chapter brief descriptions of several case studies have been included. Readers may find this section particularly interesting. Every method has been discussed using two numerical examples followed by one self-test exercise problem. A careful selection of exercise problems covers the entire content of the corresponding chapter. The book is expected to be a promising text on Management Science (or Decision Science) in the national as well as international market at both undergraduate and graduate levels.